ORGANIZATIONAL CULTURAL INTELLIGENCE, INTERNATIONAL OPPORTUNITY RECOGNITION AND BRAND INTERNATIONAL COMPETITIVENESS OF COFFEE ENTERPRISES - Hu, Rui (วารสารปัญญาภิวัฒน์, 2026)
This study aims to discuss the impact of organizational cultural intelligence on brand international competitiveness of Chinese coffee enterprises. By using the combination of multi-round large-sample questionnaire survey and qualitative comparative analysis method, this study makes an in-depth investigation into coffee enterprises, analyzes the mechanism of brand international competitiveness improvement of coffee enterprises from the perspective of organizational culture intelligence, and further discusses the mediating effect of international opportunity recognition. The research results revealed that enterprises with a high level of organizational culture intelligence can identify new opportunities quickly and effectively, and tend to have stronger brand competitiveness in the international market competition. Therefore, the corresponding solutions are proposed to solve the bottleneck problem of “Three Low and One High” of Chinese coffee enterprises and improve their brand international competitiveness.